Mobile Learning for Engineering Education Reform (Sains Humanika, 2017)
Due to the numerous challenges facing engineering education, it should be reformed especially in engineering curricula, teaching methods and teachersâ€™ preparation. Regarding the mobile learning innovations and lack of research about its capabilities for facilitating engineering education reform, this paper aims to investigate and synthesize mobile learning potentials to support the reforming process by reviewing existing studies. The reviewed papers were analyzed using theme analysis method. Providing more opportunities to achieve professional skills and improving personal, authentic and collaborative learning activities, enhancing the quality, accessibility and acceptability of learning resources are the main benefits of mobile learning for engineering education.Â Â
Keywords: Educational technology; engineering education; mobile learning